Removal Technique of Penetrating Nail in Head: A Case Report - Agus Suhendar; Effendy Effendy (International Journal of Integrated Health Sciences, 2023)
Objective: To present a unique case involving a 44-year-old man who sustained a penetrating head injury after nailing his head with a hammer. Despite the severity of his injury, the patient underwent successful surgical treatment and experienced a good recovery.